Silver nanoparticle fate in mammals: Bridging in vitro and in vivo studies - Marchioni, Marianne; Jouneau, Pierre-Henri; Chevallet, Mireille; Michaud-Soret, Isabelle; Deniaud, Aurélien (Coordination chemistry reviews, 2018)
[Display omitted] •The increasing use of Ag nanoparticles is raising safety concerns for Human.•AgNPs are subject to various transformations before and after absorption in mammals.•A gap exists between in vitro and in vivo studies leading to discrepancies.•Cutting-edge imaging methods and speciation analysis provide clues for in vivo study. Silver nanoparticles (AgNPs) are exponentially used in various consumer products including medical devices. This production leads to an increasing human exposure to silver in different forms. Indeed, AgNPs are subject to various transformations in aqueous aerobic conditions that trigger the production of Ag(I) species. The main environmental transformation produces the non-toxic species silver sulfide. Transformations occurring in mammals are more diverse and mainly depend on the interaction of AgNPs with thiol, chloride and proteins. Any of these species have a different impact on AgNPs and induces AgNP dissolution into Ag(I) species, aggregation and/or stabilization. The transformations occurring also depend on the exposure route. The main one is dietary but medical exposure is also growing with the massive use of nanosilver as biocide in medical devices. For the former, AgNP modifications and Ag distribution has been extensively studied using in vitro and in vivo models, while data related to medical use of nanosilver are scarce. However, most of the in vitro and in vivo data often remain inconsistent. In this review, we describe both in vitro, in cellulo and in vivo data about AgNP transformations, silver speciation and biodistribution. We try to reconcile all these data and describe the latest methods for the future studies of AgNP fate in mammals.